Melanoma of the eye - Stankiewicz, Andrzej; Figurska, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2003)
Melanoma is the most common eye malignant neoplasm in adults, comprising 20% of all malignant melanomas. The tumor occurs 8 times more frequently in white than in black people. Most melanomas are diagnosed after forty years of age. In contrast to retinoblastoma, hereditary transmission of melanoma is exceedingly rare. Genetic basis of melanoma. Melanoma develops from neuroectodermal melanocytes, which displace to the conjunctiva, iris, ciliary body and choroid during embryogenesis. The tumor stems from melanocytic nevi or as transformation de novo. Oncogenes located on 3, 6, 9, 11 and 18 chromosome are responsible for melanoma growth. Many authors indicate great importance of p 53 suppressor gene mutation in melanoma formation. p 53 gene product protects DNA chain against the damage. Localisation, morphology and treatment of malignant melanoma of the eye. Conjunctival melanomas, comprising 2% of eye melanomas, are diagnosed after fifty years of age. They stem from primary melanosis (50%) or melanocytic benignant nevi (25%). In 25% conjunctival melanoma is the primary tumor. Metastases of conjunctival melanoma are often localised in surrounding lymphadens as in skin melanoma. Local resection with the 2–3 mm margin of healthy tissue is a recognised treatment in the case of conjunctival melanoma. Malignant melanoma of the iris as a pigmented or unpigmented tumor is typically situated in the lower part of the iris. Diffusely growing melanomas often cause heterochromia iridis and usually lead to symptoms of glaucoma. Most malignant melanomas of the iris are composed of spindle cells of type A or B. Wide iridectomy, goniosydectomy, iridotrabeculectomy are used in the surgical treatment of iris melanoma. Most uveal melanomas arise from the choroid. There are two basic growth patterns of choroidal melanoma: localised tumor and diffused flat melanoma. Choroidal melanoma stems in most cases from eye melanosis, eye-skin melanosis or melanocytic nevi. Most risk factors of uveal melanoma are presented in the paper. The authors describe methods of treatment such as photocoagulation, transpupillary thermotherapy, photodynamic therapy, radiotherapy, brachytherapy, local resection and enucleation.